Non-aneurysmal abdominal aortic rupture in a patient with Marfan syndrome. (September 2016) - Ng, Eugene; Tewksbury, Robert; Choong, Andrew MTL; Walker, Philip J; Aziz, Maged
Aortic rupture in the presence of aneurysmal disease is well understood and extensively described in the literature. However, aortic rupture in a non-aneurysmal aorta is far less common. In the few reported cases, perforations are believed to result from a penetrating atheromatous ulcer of the aorta. We describe a rare case of non-aneurysmal aortic rupture in a 68-year-old man with Marfan syndrome and a history of proximal aortic surgery. The urgent need for hemorrhage control precluded any consideration of an endovascular repair.